The Translation Analysis In Sentence Patterns Found In The Novel â€œBuddhaâ€ - juliarta, I Made juliarta (International Journal of Linguistics and Discourse Analytics, 2021)
This study aims to: (i) analyze the tree diagram structure of sentence patterns found in the data source, (ii) analyze the types of translation shifts of sentence patterns in the translation process from source language into target language. The novel entitled â€œBuddhaâ€ is a non-fiction book by Karen Armstrong. It tells about an examination of the life, times, and lasting influence of Siddharta Gautama with core tenets of Buddhism introduced throughout history. This research focuses on The Syntax Analysis and Its Translation Found on Sentence Patterns in the Novel entitled â€œBuddhaâ€. This study aims at analyzing the tree diagram structure and the types of translation shifts found in the novel entitled â€œBuddhaâ€. The analysis uses the theory of sentence patterns from Quirk and Greenbaum and the theory of translations shift proposed by Catford. The process of collecting data was started by reading the entire data source to understand the story in the novel entitled â€œBuddhaâ€ and observe the data of sentence patterns that can be taken from the story entitled â€œBuddhaâ€. In the method of collecting data, the data source was read to find out complex sentences and simple sentence found in the story. The finding of the research is that there are seven sentence patterns that are translated by applying unit shift. The researcher uses the theories to support this research. Those are syntax, types of sentences, sentence pattern, tree diagram, and relevant previous studies. Syntax is stated as one of the branches that focus on the sentence structure. This research study uses theory of translation shift proposed by Catford